BODY IMAGE BERHUBUNGAN DENGAN INDEKS MASSA TUBUH, TAPI TIDAK DENGAN WAIST TO HIP RATIO PADA VEGETARIAN PUTRI DI SURABAYA - Anastasia Prastiwi Switeng Siwi Siwi; Triska Susila Nindya (Universitas Airlangga, 2016)
Dissatisfaction with body shape are common among young women. Therefore, they always trying to get their ideal body shape. One of the effort to get ideal body shape is applying vegetarian diet. This study aimed to analyze the association between body image and body mass index ( BMI) and waist to hip ratio (WHR) among young women vegetarian. The study was a cross sectional with quantitative approach among 32 young women vegetarian in Surabaya. The body image perception was obtained using a questionnaire. The nutritional status was obtained from weight and height measurement, and WHR was obtained by measuring waist and hip circumference. This study showed that as many as 23 respondents (71.9%) had a positive perception of body image, as many as 22 respondents (68.7%) had WHR <0.8 cm, and a total of 19 respondents (59.3%) had a normal BMI. There was an association between body image and BMI (p=0.014), but there was no association between b ody image and WHR (p=0.653). This study conclude that b ody image is associated to BMI but not WHR